KRITIK MITOS TENTANG PEREMPUAN PADA ‘AKAR PULE’ KARYA OKA RUSMINI - Yuliati, Ana (Program Studi Pendidikan Bahasa Indonesia STKIP-PGRI Bangkalan, 2019)
Oka Rusmini is one of the Indonesian women writers from Bali. His figure and works are phenomenal and often controversial because they raise a number of issues of old-fashioned Balinese customs and traditions that are detrimental to women, especially in the griya environment, home of the Brahmins. This study aims to describe the form and meaning of myths about women in 'Akar Pule' by Oka Rusmini. The form of myth contained in 'Root Pule' by Oka Rusmini consists of two fields, namely the field of anthropology and sociology. Both fields of myth are closely related to women. the form of myth in the field of anthropology is closely related to the rituals that must be performed by women, while in the field of sociology the form of myths closely related to women is a curse, a jinxed bearer.